Metabolic Phenotyping of Adipose-Derived Stem Cells Reveals a Unique Signature and Intrinsic Differences between Fat Pads - Camille Lefevre; Baptiste Panthu; Danielle Naville; Sylvie Guibert; Claudie Pinteur; Bénédicte Elena-Herrmann; Hubert Vidal; Gilles J. P. Rautureau; Anne Mey (Stem Cells International)
White adipose tissues are functionally heterogeneous and differently manage the excess of energy supply. While the expansion of subcutaneous adipose tissues (SAT) is protective in obesity, that of visceral adipose tissues (VAT) correlates with the emergence of metabolic diseases. Maintained in fat pads throughout life, adipose stem cells (ASC) are mesenchymal-like stem cells with adipogenesis and multipotent differentiation potential. ASC from distinct fat pads have long been reported to present distinct proliferation and differentiation potentials that are maintained in culture, yet the origins of these intrinsic differences are still unknown. Metabolism is central to stem cell fate decision in line with environmental changes. In this study, we performed high-resolution nuclear magnetic resonance (NMR) metabolomic analyses of ASC culture supernatants in order to characterize their metabolic phenotype in culture. We identified and quantified 29 ASC exometabolites and evaluated their consumption or secretion over 72 h of cell culture. Both ASC used glycolysis and mitochondrial metabolism, as evidenced by the high secretions of lactate and citrate, respectively, but V-ASC mostly used glycolysis. By varying the composition of the cell culture medium, we showed that glutaminolysis, rather than glycolysis, supported the secretion of pyruvate, alanine, and citrate, evidencing a peculiar metabolism in ASC cells. The comparison of the two types of ASC in glutamine-free culture conditions also revealed the role of glutaminolysis in the limitation of pyruvate routing towards the lactate synthesis, in S-ASC but not in V-ASC. Altogether, our results suggest a difference between depots in the capacity of ASC mitochondria to assimilate pyruvate, with probable consequences on their differentiation potential in pathways requiring an increased mitochondrial activity. These results highlight a pivotal role of metabolic mechanisms in the discrimination between ASC and provide new perspectives in the understanding of their functional differences.